Ambient Assisted Living 9. AAL-Kongress, Frankfurt/M, Germany, April 20 - 21, 2016 - Wichert, Reiner; Mand, Beate; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
In this book, leading authors in the field discuss the habitats of tomorrow. These habitats will be connected through autonomous and assistive systems, turning habitats into health resorts. This book discusses how assistance technologies enable a smooth transition from comfortable health support to medical or nursing care. The contributions have been chosen and invited at the 9th AAL congress, Frankfurt. .
Integration of Stationary and Wearable Support Services for an Actively Assisted Life of Elderly People: Capabilities, Achievements, Limitations, Prospects - A Case Study -- QuoVadis - Definition of Requirements and Conception for Interconnected Living in a Quarter for Dementia Patients -- Invisible Human Sensing in Smart Living Environments using Capacitive Sensors -- LivingCare - An autonomously learning, human centered home automation system: Collection and preliminary analysis of a large dataset of real living situations -- New Approaches for Localization and Activity Sensing in Smart Environments -- Technology supported geriatric assessment.
Keywords: Biomedical engineering; Economic development; Aging; Geriatrics; Medical informatics; Biomedical Engineering and Bioengineering; Economic Development, Innovation and Growth; Ageing; Geriatrics; Health Informatics